Maternal and Environmental Risk Factors for Congenital Heart Diseases in Offspring: A Review Article - Zielińska, Agnieszka; Kamińska, Zuzanna Zofia; Blecharczyk, Małgorzata; Mrozek, Martyna; Zydlewski, Igor; Pacanowska-Trawnicka, Martyna; Jakimowicz, Aleksandra; Malcher, Aleksandra (Quality in Sport, 2026)
Background. Congenital heart diseases (CHDs) are the most common congenital anomalies and a leading cause of infant morbidity and mortality. Although genetic factors play an important role, many cases remain unexplained, highlighting the contribution of maternal and environmental exposures. Aim. This review aims to provide a comprehensive and up-to-date synthesis of non-genetic maternal risk factors associated with CHDs in offspring. Material and methods. A literature review was conducted using PubMed, NCBI and Google Scholar, including studies published between 2010 and 2025. Systematic reviews, meta-analyses, cohort and case-control studies evaluating maternal and environmental exposures were analyzed. Results. Evidence indicates that maternal diabetes and obesity are key risk factors, with clear dose-response relationships. Additional contributors include smoking (active and passive), alcohol consumption, infections, fever, psychological stress and environmental pollutants. Protective effects of folic acid and multivitamin supplementation were also observed. Interaction effects between environmental exposures and parental behaviors further increase CHD risk. Conclusions. CHD etiology is multifactorial, involving modifiable maternal and environmental factors. Identification and reduction of these exposures, particularly during early pregnancy, are essential for prevention. Further prospective and mechanistic studies are needed to clarify causal pathways and improve risk reduction strategies.